Mutual Legal Assistance Pada pemberantasan Cyber Crime Lintas Yurisdiksi di Indonesia - Bambang Hartono; Recca Ayu Hapsari (Faculty of Law, Universitas Pattimura, 2019)
The development of global information and transportation technology is accompanied by the development of criminal acts that no longer recognize jurisdictional boundaries, so that the response requires joint handling of world countries. Mutual assistance in criminal matters is one way to stop fraudulent acts of criminals who want to hide assets. The implementation of the Mutual Legal Assistance System was realized in the implementation of Law Number 1 of 2006 concerning Reciprocal Assistance in Criminal Issues, namely by establishing cooperation with countries that have the potential to be used as hiding places or to save income from the crime. This has become one of the efforts to prevent cross-jurisdictional cyber crime by implementing a Mutual Legal Assistance System